4 - Covid-19 Lockdown and the ‘Work-From-Home’ Approach: The Effect on Nigerian Academics - Tolulope Osinubi; Cleopatra Ibukun; Titus Ojeyinka (Africa Development, 2023)
This article investigates the effect of the Covid-19 lockdown and the ‘work- from-home’ approach on academic activities in Nigeria, using bivariate and multivariable regression. The results show that factors such as inadequate power supply, electricity access, workspace and access to research materials, health status and care for children and the elderly during the Covid-19 lockdown were significantly associated with a decline in the time devoted to academic work. On the other hand, virtual teaching or learning and the ability to work from home more often had positive and statistically significant effects on weekly work hours. The study also finds that Covid-19 lockdowns had a stronger negative effect on female researchers than their male counterparts. The implication is that a prolonged lockdown will harm the education system in Nigeria by negatively affecting research outcomes in terms of weekly work hours. Thus, the recommendations emanating from the findings are discussed in the article.